2000
DOI: 10.1073/pnas.210395997
|View full text |Cite
|
Sign up to set email alerts
|

Life in extreme environments: Hydrothermal vents

Abstract: Eruption of volcanic rocks at the midocean ridges is the major mechanism by which heat is lost from the interior of the Earth. Approximately one-third of the heat is removed from the spreading centers by convective circulation of seawater (1). The magnitude of this heat loss requires that the entire volume of the oceans circulates through the midocean ridges in approximately 10 million years. Seawater interaction with volcanic rocks at near 400°C results in substantial chemical flux and makes an important cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 17 publications
0
63
0
3
Order By: Relevance
“…In addition, our investigators have found that two amino acid changes in a family 42 ␤-galactosidase (BgaB) expand its temperature range by 20°C (N. Panasik, unpublished data). These data all point to the notion that amino acid sequence and gross structural comparisons will not lead to answers about enzyme adaptation to different thermal pressures (2,25,(48)(49)(50). Instead, there is growing evidence (50) that these answers will be found in subtle, synergistic, and cooperative intramolecular interactions.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, our investigators have found that two amino acid changes in a family 42 ␤-galactosidase (BgaB) expand its temperature range by 20°C (N. Panasik, unpublished data). These data all point to the notion that amino acid sequence and gross structural comparisons will not lead to answers about enzyme adaptation to different thermal pressures (2,25,(48)(49)(50). Instead, there is growing evidence (50) that these answers will be found in subtle, synergistic, and cooperative intramolecular interactions.…”
Section: Discussionmentioning
confidence: 97%
“…These environments provide unique models for understanding living strategies in extreme environments and for exploring questions regarding the origins and limits of life on this planet or the potential for extraterrestrial life (2,3). The base of the deep-sea life pyramid in the vent environments consists of chemolithoautotrophic microorganisms, which are fueled by geochemical energy, such as H 2 S and H 2 .…”
mentioning
confidence: 99%
“…Rather than confining experiments to laboratory simulations, we recommend that such studies should be undertaken in the field because the results will provide additional evidence for comparing the relative plausibility of the two alternative sites for the origin of life. (Wächtershäuser, 1992;Zierenberg et al, 2000).…”
Section: Testing Alternative Hypothesesmentioning
confidence: 99%
“…Vent minerals are a source of transition metals with potential catalytic activity when incorporated into peptides (Zierenberg et al, 2000).…”
Section: Testing Alternative Hypothesesmentioning
confidence: 99%